Frans Hinskens, Johan Taeldeman (eds.). Language and Space: An International Handbook of Linguistic Variation Volume 3: Dutch - de Louw, Robertus; Szczypińska, Małgorzata; Wiercińska, Katarzyna (Werkwinkel, 2017)
Review: Frans Hinskens, Johan Taeldeman (eds.). Language and Space: An International Handbook of Linguistic Variation, Volume 3: Dutch Berlin/Boston: De Gruyter Mouton 2013, 937 pp., ISBN 978 3110 180 053.